Promoting gallery walk to foster students writing skill - Ujang Amrullah; Rahma Dianti (Relawan Jurnal Indonesia, 2021)
This research highlighted the application of gallery walk to enhance students’ achievement in writing a recount text. The goal of this research are to assess whether or not the use of gallery walk could foster the students’ writing score and to find the significant difference in students’ recount text writing achievement between those who were taught by using gallery walk and that of those who were not. This research used a quasi-experimental research design with no random sampling. The samples were taken by using purposive sampling, consisting of 37 students for the experimental and control groups. The data were collected by using a written test and administered before and after the treatment. To verify the hypotheses, the data were analyzed using paired sample t-test and independent sample-test and the calculation was done using SPSS program. The result showed that the promotion of gallery walk could foster students’ achievement in writing a recount text and there was a significant difference between posttest results of both groups.